متطلبات تطبيق المواصفة ISO 9001:2008)) في الشركة العامة لصناعة الزيوت النباتية دراسة حالة - بريهي فارس كريم; كشيش ميس عبد الامير (Journal of Economics and Administrative Sciences, 2018)
The research is to use the specifications and detection of the main and secondary causes of the problems that lead to the weakness and low quality of local production in Iraqi companies and develop appropriate solutions to them, as Iraqi companies suffer from the low quality of production, And the adoption of the requirements of ISO 9001: 2008, which contributes to the development of production processes within the company, and through the field co-operation and survey conducted for public companies affiliated to the Ministry of Industry and Minerals, The importance of the research through the statement of the most important problems facing the General Company for vegetable oil industry in terms of low and weak in production quality and weak ability to compete imported products, and the most important conclusions reached by the researcher shows that the quality processes within the department (quality and ISO) without other sections The company’s lack of interest in the development and training of its employees on the quality system and the lack of financial allocations for training courses and the non-use of technology to examine the products, but limited to the usual physical and chemical methods. Due to the weakness of the technology in the company and recommends the researcher to increase the incentive of the worker through the equivalent of the active worker and the efficiency and experience and high costs and increased by senior management to achieve and improve the system of high quality. The work of courses and seminars to increase the experience and efficiency of staff working in technical departments.